The Effect of Corporate Governance, Company Growth and Debt Policy on Financial Performance in Technology Sector Companies Listed on the Indonesian Stock Exchange For the Period 2017-2021 - Y, Amzi J.M.; Ispriyahadi, Heri; Kholil, Kholil (SEAN Institute, 2024)
Good Corporate Governance constitutes a framework that positively influences a company's financial performance. This research aims to ascertain and analyze the impact of Corporate Governance, company growth, and debt policy on technology sector companies listed on the Indonesia Stock Exchange from 2017 to 2021. The research utilizes secondary data extracted from annual reports accessible on the IDX website via www.idx.co.id covering a five-year period (2017-2021). Statistical analysis is conducted employing SPSS Version 25.0. Hypothesis testing is carried out using the F test and T test. Partial results indicate that the independent board of commissioners (DKI) and company growth (PP) significantly affect financial performance (ROA) among companies listed on the IDX during 2017-2021. Conversely, institutional ownership (KI), managerial ownership (KM), and debt policy (DER) demonstrate no significant impact on financial performance (ROA) within the same companies and period. Thus, it is advisable for companies to sustain and enhance their financial performance to achieve profitable outcomes, involving all stakeholders in the process.